Influence of Impregnation Processes on Ruthenium–Molybdenum Carbon Catalysts for Selective Hydrodeoxygenation of Biomass‐Derived Sorbitol into Renewable Alkanes. Issue 9 (31st July 2018) - Weng, Yujing; Wang, Tiejun; Duan, Peigao; Wang, Chenguang; Wang, Feng; Liu, Qiying; Chen, Lungang; Wang, Haiyong; Liang, Zheng; Ma, Longlong
Abstract: Sorbitol, as a C6 sugar related compound derived from cellulose, is regarded as a promising biomass‐derived substrate and has characteristically higher oxygen content than in fossil‐based resources. In this work, ruthenium–molybdenum carbon catalysts prepared by different impregnation processes were employed and extensively studied in a trickle‐bed reactor for sorbitol hydrodeoxygenation (HDO). Interestingly, these catalysts afforded remarkably different HDO performance. Ruthenium–molybdenum catalysts prepared by ultrasonic treatment and calcination obtained high HDO performance in sorbitol conversion with 79.8 % carbon yield of C5/C6 alkanes (pentane and hexane), almost twice that of ruthenium–molybdenum catalysts prepared without using a calcination processes. Therefore, a series of characterization studies (N2 ‐adsorption, XRD, HRTEM, XPS, H2 ‐TPR, CO‐TPD, NH3 ‐TPD, Py‐IR spectra, etc.) were performed over relevant catalysts to study the catalytic mechanism. The results suggest that prior calcination offers a better chance for the proximity between Ru and Mo precursors to produce the bimetallic catalytic structure Ru–MoO x, which produces high HDO performance. Abstract : Sweet catalysis : Ru–MoO x /C catalysts from different impregnation processes were carefully studied and extensively employed for sorbitol conversion to C5/C6 alkanes in trickle‐bed reactor. The results suggest that prior calcination offers a better chance for the proximity between Ru and Mo precursors to produce the bimetallic catalytic structure Ru–MoO x, which produces high HDO performance towards biofuels synthesis.